Entities and axes of action in the popular and solidarity economy: Cayambe case, Ecuador - Gómez, Javier Herrán; Salgado Guerrero, Bernardo; Torres Toukoumidis, Angel (Cooperativismo & Desarrollo, 2020)
This research provides an exhaustive description of the presence of the popular and solidarity economy in Cayambe, Ecuador. For this, the qualitatively focused case study presents the entities and axes of action as variables through which the study was carried out, including the collection of documentation from local and regional institutions, in addition to the participating in observation for more than 25 years in that context. The results show that although savings and credit cooperatives, associative entities and solidarity entities are based on the development of the popular and solidarity economy, the opposite occurs with the community banks and the popular economic units. As for the second variable, the axes of action are organized into technical-practical and political-social, in which the technological development of the community accompanied by empowerment is respectively promoted. In conclusion, this study seeks to promote the follow-up of cases where the approximation of the popular and solidary economy, with the communities and their prospective settlement in the community, can be evidenced.